In-vitro and In-vivo Determinations of Sun Protection Factors (SPF) of Skin Lotions Containing Mountain Papaya Fruit and Mangosteen Peel Ethanolic Extract - Heru Sasongko; Natasya Advaita; Ratih Guswinda Lestari; Karimah Umar Aidid (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Indonesia is a high sun exposure country. Exposure to ultraviolet (UV) causes various kinds of skin disorders such as erythema, sunburn, aging, and cancer. Mountain papaya fruit (Vasconcellea pubescens A.DC.) and mangosteen peel (Garcinia mangostana L.) contains metabolite compounds that can protect the skin from sunlight because of its antioxidants activity. The purpose of this study to determine whether the combination of the mountain papaya fruit and mangosteen peel extracts in skin lotion can be used as sun protectors through the in-vitro and in-vivo study. The experiment was done by extracting the mountain papaya fruit and mangosteen peel through the maceration method. The extracts were formulated into skin lotion in three different formulas with the ratio of mountain papaya fruit extract: mangosteen peel extract as follows F1(1:1), F2(1:3), and F3(3:1). In vitro test was done by using UV-VIS spectrophotometry to determine the SPF value and in vivo test was used erythema-induced rats by exotera beam light. The result of in vitro test gained a high enough SPF value for all three formulas F1=23,23; F2=21,70 and F3=28,64 and the result of in vivo test showed that all three formulas did not indicate the existence of erythema value. It can be concluded that three skin lotion formulas containing mountain papaya fruit and mangosteen peel ethanol extract have the effect of sun protection.